Implementation of Waste Bank Management Policy in Tasikmalaya City - Khumayah, Siti (International Journal of Science and Society, 2025)
The Waste Bank serves as both a platform to address community issues and a facility for waste management based on the principles of reduce, reuse, and recycle (3R). It's utilized by local governments for educational purposes, fostering behavioral changes in waste management, and promoting circular economy practices. Managed jointly by the community, businesses, and the government, it's a collaborative effort aimed at tackling waste issues. A qualitative study analyzing waste bank management policies in Tasikmalaya City reveals a successful implementation driven by robust cooperation between the government and the community in waste management endeavors. Even though there are still obstacles such as the lack of clear regulations and inadequate waste processing methods, the Waste Bank has succeeded in changing people's view of waste into something that has economic value. To be more effective, regulations, waste processing and utilization of existing facilities need to be improved. Factors such as resource availability, community participation, technological development, characteristics of Waste Bank users, economic, social, political factors and government support influence the implementation of Waste Banks. Even though there are still obstacles such as lack of resources and public understanding, with technological development, behavioral changes, government support and good strategies, waste banks have great potential to manage waste more efficiently and provide great economic and environmental benefits for the City of Tasikmalaya.